Learning organization on turnover intention through organizational commitment as a mediating variable in company x - Stevanie Ana; Saparso Saparso; Lidia Sandra (Institute of Computer Science (IOCS), 2024)
This research is motivated by the high employee turnover rate in IT companies in Indonesia caused by the Covid-19 pandemic and limitations in employee self-development due to the lack of implementation of Learning Organization culture which has little impact on Organizational Commitment. employees in a company. The purpose of this research is to find out whether Learning Organization and Organizational Commitment influence Turnover Intention and whether Organizational Commitment mediates the influence of Learning Organization on Turnover Intention. The research object in this study is Turnover Intention. In this study, the population chosen by researchers was 235 employees of PT. The data collection (sampling) technique used by researchers in this research is nonprobability sampling. By using a questionnaire distributed online via Google Form. Research data processing was carried out using a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) or called PLS-SEM using SmartPLS 4.0 software and the Baron and Kenny Mediation Method (1986). The results of this research show that Learning Organization has a significant effect on Organizational Commitment, Organizational Commitment has a significant effect on Turnover Intention, Learning Organization is not significant on Turnover Intention, and Organizational Commitment mediates the influence of Learning Organization on Turnover Intention. The nature of mediation is Partial Mediation or partial mediation. The conclusion of this research is that Organizational Commitment is a determining and strengthening factor for Employee Turnover Intention at company X, while Learning Organization is not a factor that determines Employee Turnover Intention at company X